Design and Development of an Inspection Robot for Oil and Gas Applications - Hajjaj, Sami Salama Hussen; Khalid, Ilyas Bin (International Journal of Engineering and Technology, 2018)
Pipeline or mass transport line are the chief applications which are typically involved in the oil and gas industries. After various background studies, the pipeline involved in such industries comes from a high technology design and material of use. Hence, inspection and maintenance must be done frequently to ensure the pipeline can be used in an excellent working state. The inspection on pipeline must be done before and after its maintenance. However, it is difficult to inspect within the pipe to ensure it is in good condition. Currently, various new types of technology are used for inspection purposes specifically by means of the Non-Destructive Testing, but it highly costly. Thus, this project focuses on the design and development of an inspection robot to perform a pipeline inspection. Some applications that can accommodate to the designing of a robot is that the robot is able to manoeuvre inside the pipeline wirelessly and give a visual interface while proceeding it. Therefore, this project shows the development processes included in the design and development of an inspection robot for the oil and gas applications.